An N-Myristoylated Globin with a Redox-Sensing Function That Regulates the Defecation Cycle in Caenorhabditis elegans - Tilleman, Lesley; De Henau, Sasha; Pauwels, Martje; Nagy, Nora; Pintelon, Isabel; Braeckman, Bart P.; De Wael, Karolien; Van Doorslaer, Sabine; Adriaensen, Dirk; Timmermans, Jean-Pierre; Moens, Luc; Dewilde, Sylvia (PLOS ONE, 2012)
Globins occur in all kingdoms of life where they fulfill a wide variety of functions. In the past they used to be primarily characterized as oxygen transport/storage proteins, but since the discovery of new members of the globin family like neuroglobin and cytoglobin, more diverse and complex functions have been assigned to this heterogeneous family. Here we propose a function for a membrane-bound globin of C. elegans, GLB-26. This globin was predicted to be myristoylated at its N-terminus, a post-translational modification only recently described in the globin family. In vivo, this globin is found in the membrane of the head mesodermal cell and in the tail stomato-intestinal and anal depressor muscle cells. Since GLB-26 is almost directly oxidized when exposed to oxygen, we postulate a possible function as electron transfer protein. Phenotypical studies show that GLB-26 takes part in regulating the length of the defecation cycle in C. elegans under oxidative stress conditions.